1999
DOI: 10.1016/s0042-6989(98)00306-x
|View full text |Cite
|
Sign up to set email alerts
|

Sharpness overconstancy: the roles of visibility and current context

Abstract: In a previous study we found that blurred edges presented in peripheral vision look sharper than when they are looked at directly, a phenomenon we have called peripheral sharpness overconstancy (Galvin et al. (1997). Vision Research, 37, 2035-2039). In the current study we show that when visibility of the stimulus edges is compromised by very brief presentations, we can demonstrate sharpness overconstancy for static, foveal viewing. We also test whether the degree of sharpening is a function of the current vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…In normal viewing conditions, objects in the peripheral visual space are not perceived to be very blurry though we constantly experience poor image quality in the periphery due to the existing peripheral optical errors. In fact, previous studies have shown that blurred edges are perceived to be sharper in peripheral vision (Galvin, O'Shea, Squire, & Govan, 1997;Galvin, O'Shea, Squire, & Hailstone, 1999). In this context, it should be noted that the +2.00 D in the present study was introduced over the existing peripheral refractive errors and, as the spherical equivalent in 20°eccentricity was myopic in all four subjects, gave a further increase in peripheral refraction.…”
Section: Large Field Blur Stimulus Gave No Improvement After Adaptationsupporting
confidence: 40%
“…In normal viewing conditions, objects in the peripheral visual space are not perceived to be very blurry though we constantly experience poor image quality in the periphery due to the existing peripheral optical errors. In fact, previous studies have shown that blurred edges are perceived to be sharper in peripheral vision (Galvin, O'Shea, Squire, & Govan, 1997;Galvin, O'Shea, Squire, & Hailstone, 1999). In this context, it should be noted that the +2.00 D in the present study was introduced over the existing peripheral refractive errors and, as the spherical equivalent in 20°eccentricity was myopic in all four subjects, gave a further increase in peripheral refraction.…”
Section: Large Field Blur Stimulus Gave No Improvement After Adaptationsupporting
confidence: 40%
“…Overall, the perception of blur is a complex process that depends on the eye's optical quality (i.e., aberrations) as well as both retinal and higher level neurophysiology (Ciuffreda et al, 2007; Mather & Smith, 2002; Wang & Ciuffreda, 2004, 2005a, 2005b). Motion, visual attention, sharpness overconstancy, and target attributes such as luminance, contrast, texture, and size also contribute to the perception of image blur (Christman, 1990; Galvin, O'Shea, Squire, & Hailstone, 1999; Pääkkönen & Morgan, 1994; Wang & Ciuffreda, 2004, 2005b). …”
Section: Introductionmentioning
confidence: 99%
“…Visual spatial attention is mostly focused on the fovea, so much so that eye movements are called overt attention, and we seem to confuse the phenomenal characteristics of foveal visual perception with visual perception in general. As another example, contours in peripheral vision appear sharp (3) (cf Galvin, O'Shea, Squire, & Govan, 1997;Galvin, O'Shea, Squire, & Hailstone, 1999), even though acuity, which would be thought to be at the basis of perceived sharpness, is drastically reduced there.…”
Section: Introductionmentioning
confidence: 99%